First records of two species of reef-associated mantis shrimps (Crustacea: Stomatopoda) from India - Padate, Vinay P.; Ahyong, Shane T.; Shaji, Aleesha K.; Cubelio, Sherine Sonia; Saravanane, Narayanane (Zootaxa, 2021)
The coastal marine environments in the Indian Exclusive Economic Zone harbour a rich diversity of mantis shrimps. However, several regions have not been adequately surveyed for their stomatopod faunal composition. In this paper, we report the first records of two species, Gonodactylopsis drepanophora (de Man, 1902) and Cloridina malaccensis (Manning, 1968) from Indian waters. Samples were collected using a chain dredge deployed by the Fishery Oceanographic Research Vessel Sagar Sampada on the shallow reefs (53–56 m depths) of the Andaman Sea and Bay of Bengal during August–November 2019. Gonodactylopsis drepanophora was previously known only from Indonesia, and Cloridina malaccensis from Southeast Asia, New Caledonia and Madagascar.